Obstacles and opportunities for targeting the effector T cell response in type 1 diabetes. (July 2016) - Buckner, Jane H.; Nepom, Gerald T.
Abstract: Autoreactive lymphocytes display a programmed set of characteristic effector functions and phenotypic markers that, in combination with antigen-specific profiling, provide a detailed picture of the adaptive immune response in Type 1 diabetes (T1D). The CD4+ T cell effector compartment (referred to as "Teff" in this article) has been extensively analyzed, particularly because the HLA genes most strongly associated with T1D are MHC class II alleles that form restriction elements for CD4+ T cell recognition. This "guilt by association" can now be revisited in terms of specific immune mechanisms and specific forms of T cell recognition that are displayed by Teff found in subjects with T1D. In this review, we describe properties of Teff that correlate with T1D, and discuss several characteristics that advance our understanding of disease persistence and progression. Focusing on functional disease-associated immunological pathways within these Teff suggests a rationale for next-generation clinical trials with targeted interventions. Indeed, immune modulation therapies in T1D that do not address these properties of Teff are unlikely to achieve durable clinical response. Highlights: CD4 effector T cells are programmed to be pathogenic in T1D. HLA Genes associated with T1D drive the selection of islet specific CD4 T cells in T1D. T1D risk variants promote development and expansion of pathogenic T cells. Effector T cells in T1D are resistant to suppression by regulatory T cells. Immunotherapies are being used to target autoreactive Teff in T1D.